Debt Overhang in Emerging Europe? - Brown, Martin; Lane, Philip R. (2012)
This paper assesses the extent to which debt overhang poses a constraint to economic activity in Emerging Europe, as the region emerges from the recent financial and economic crisis. At the macroeconomic level, it finds that the external imbalance problem for Emerging Europe has been in most cases more one of flows (high current account deficits in the pre-crisis years) rather than large stocks of external debt. A high reliance on equity funding means that net external debt is far lower than net external liabilities. Domestic balance sheets have expanded quite rapidly but sector liabilities remain relatively low compared with advanced economies. With the important exception of Hungary, public debt levels also remain relatively low in Emerging Europe. At the microeconomic level, the potential for debt overhang in the corporate sector is limited to a few countries: Latvia, Lithuania, Estonia, and Slovenia. Due to the low incidence of household debt, hardly any country, except Estonia, seems to face a threat of debt overhang in the household sector. The strong increase in non-performing loans compared with pre-crisis bank profitability suggests that debt overhang in the banking sector is a threat in Ukraine, Latvia, Lithuania, Hungary, Georgia, and Albania. Financial integration of Emerging Europe seems to have contributed to the transmission of the crisis to the region. At the same time, this integration is helping the region in managing the crisis by concerted actions of the major players.